Analysis of the Influence of Poverty, Unemployment Rate, and Economic Growth on the Human Development Index in West Nusa Tenggara Province - Maulana, Muhammad Firman; Huda, Syamsul (Journal of Regional Economics and Development, 2025)
This study aims to analyze the influence of Poverty, Unemployment Rate, and Economic Growth on the Human Development Index (HDI) in West Nusa Tenggara Province during the period 2014-2024. The research method used was multiple linear regression analysis to identify the relationship and significance between variables with the SPSS version 25 tool. The results of the study show that Poverty has a negative influence on the Human Development Index. Meanwhile, the Unemployment Rate does not show a significant influence on the Human Development Index. Economic Growth Found to Have a Positive Effect on Economic Growth, This study provides important implications for policy making in an effort to improve the Human Development Index in West Nusa Tenggara Province through an integrated handling of poverty and unemployment problems.